Longer and Deeper Desaturations Are Associated With the Worsening of Mild Sleep Apnea: The Sleep Heart Health Study - Karhu, Tuomas; Myllymaa, Sami; Nikkonen, Sami; Mazzotti, Diego R.; Töyräs, Juha; Leppänen, Timo (Frontiers in Neuroscience, 2021)
Study Objectives: Obesity, older age, and male sex are recognized risk factors for sleep apnea. However, it is unclear whether the severity of hypoxic burden, an essential feature of sleep apnea, is associated with risk for sleep apnea worsening. Thus, we investigated our hypothesis that the worsening of sleep apnea is expedited in individuals with more severe desaturations. Methods: Blood oxygen saturation (SpO2) signals of 805 Sleep Heart Health Study participants with mild sleep apnea (5≤oxygen desaturation index (ODI)<15) were analyzed at the baseline and after the mean follow-up time of 5.2 years. Linear regression analysis, adjusted for relevant covariates, was utilized to study the association between baseline SpO2-derived parameters and change in sleep apnea severity, determined by change in ODI. SpO2-derived parameters, consisting of ODI, desaturation severity (DesSev), desaturation duration (DesDur), average desaturation area (avg. DesArea), and average desaturation duration (avg. DesDur), were standardized to enable comparison between the parameters. Results: In the group consisting of both men and women, avg. DesDur (β=1.594, p=0.001), avg. DesArea (β=1.316, p=0.004), DesDur (β=0.998, p=0.028), and DesSev (β=0.928, p=0.040) were significantly associated with sleep apnea worsening, whereas ODI was not (β=-0.029, p=0.950). In sex-stratified analysis, avg. DesDur (β=1.987, p=0.003), avg. DesArea (β=1.502, p=0.024), and DesDur (β=1.374, p=0.033) were significantly associated with sleep apnea worsening in men. Conclusions: Longer and deeper desaturations more likely expose to the worsening of sleep apnea. This information could be useful in the planning of follow-up monitoring or lifestyle counseling in an early stage of the disease.